2000
DOI: 10.1002/(sici)1099-1085(200003)14:4<669::aid-hyp965>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Measuring interception loss and canopy storage in dryland vegetation: a brief review and evaluation of available research strategies

Abstract: Abstract:The interception storage capacity has been measured for a range of dryland plants. Interception losses over time, however, arise in rain events that deliver either less or more than the canopy capacity. The fate of water in these cases depends on the eciency with which the intercepted water is returned to the atmosphere by evaporation from the plant canopies. Two primary methods to estimate interception losses are (i) calibrated process-based models of interception and evaporative loss and (ii) direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 37 publications
3
140
1
4
Order By: Relevance
“…They have developed effective physiological drought tolerance by reducing water loss, e.g., through adjusting their photosynthetic and transpiration rate by regulating stomatal conductance and abscisic acid (ABA), titling their osmotic equilibrium by regulating the concentration of soluble sugars and inorganic ions, and removing free radicals (Ma et al, 2004. The stemflow, a vital ecohydrological flux, is involved in replenishing soil water at shallow and deep layers (Pressland, 1973), particularly the root zone (Whitford et al, 1997;Dunkerley, 2000;Yang, 2010), even during light rains (Li et al, 2009). It might allow the endemic shrubs to remain physically active during drought spells (Navar and Bryan, 1990;Navar, 2011).…”
Section: Yuan Et Al: Comparisons Of Stemflow and Its Bio-/abioticmentioning
confidence: 71%
See 2 more Smart Citations
“…They have developed effective physiological drought tolerance by reducing water loss, e.g., through adjusting their photosynthetic and transpiration rate by regulating stomatal conductance and abscisic acid (ABA), titling their osmotic equilibrium by regulating the concentration of soluble sugars and inorganic ions, and removing free radicals (Ma et al, 2004. The stemflow, a vital ecohydrological flux, is involved in replenishing soil water at shallow and deep layers (Pressland, 1973), particularly the root zone (Whitford et al, 1997;Dunkerley, 2000;Yang, 2010), even during light rains (Li et al, 2009). It might allow the endemic shrubs to remain physically active during drought spells (Navar and Bryan, 1990;Navar, 2011).…”
Section: Yuan Et Al: Comparisons Of Stemflow and Its Bio-/abioticmentioning
confidence: 71%
“…Dryland shrubs generally experienced several wetting-drying cycles (Cui and Caldwell, 1997) when rains were sporadic. As an important source of rhizosphere soil moisture at dryland ecosystems (Dunkerley, 2000;Yang, 2010;Návar, 2011;Li et al, 2013), a considerable amount of stemflow could be produced by various species and infiltrated into deep soil during heavier rains. However, during lighter rains, the larger amount stemflow produced in more efficient manner might benefit xerophytic shrubs, as more soil moisture could be recharged especially at the root zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the rainfall events causing these flood pulses are significantly above-average, and the vegetation cover is relatively sparse, it can be assumed that interception of rainfall from the surface of vegetation is negligible (Dunkerley, 2000).…”
Section: <Figure 3 Here Please>mentioning
confidence: 99%
“…Canopies of woody-plants may increase interception of rainfall (Dunkerley 2000), increase infiltration (Bhark and Small 2003) and alter the balance between evaporation and transpiration (Huxman et al 2005). We observed that the presence of Cynara was associated with greater growing-season ET (Fig.…”
Section: Discussionmentioning
confidence: 99%